A Retrospective Analysis of 25 Cases With Peripheral Nerve Field Stimulation for Chronic Low Back Pain and the Predictive Value of Transcutaneous Electrical Nerve Stimulation for Patient Selection. Issue 5 (7th December 2018) - Schwarm, Frank P.; Stein, Marco; Uhl, Eberhard; Maxeiner, Hagen; Kolodziej, Malgorzata A.
Abstract : Objective: Transcutaneous electrical nerve stimulation (TENS) and peripheral nerve field stimulation (PNFS) may be proposed to patients with chronic lumbar pain refractory to conventional treatment. Aim of this study was to assess the importance of preoperatively treatment with TENS as a predictive value for later successful PNFS and impact of PNFS in follow‐up of 12 months. Methods: Between 2012 and 2016, a retrospective analysis of 25 patients with chronic lumbar pain and implantation of a PNFS‐system was performed. Pain intensity (NRS), health‐related quality of life (EQ‐5D‐5L), Oswestry disability index (ODI), actual mood state scale (ASTS), and treatment satisfaction (CSQ‐8) were assessed pre/postoperatively, after 6 and 12 months. TENS use before surgery was assessed. Results: The cohort consisted of 25 patients with a median age of 56 years (IQR 25‐75 51–63). In a subgroup analysis, 18 patients used TENS before surgery, 7 did not use TENS and were excluded. No pain relief was observed in 14 patients. Ten of these patients showed later positive effect in PNFS trial stimulation. In four patients, pain relief with TENS was seen. One patient later on had no benefit after PNFS trial, three had sufficient pain relief. In the whole cohort, five patients had no benefit after PNFS trial, in 20 patients a neurostimulator was implanted. NRS, EQ‐5D‐5L, and ODI measures showed significant improvement in the whole follow‐up after PNFS implantation. ASTS scale showed an increase of values for positive mood and a reduction in values for sorrow, fatigue, and anger. In 55%, a sustained reduction in demand for analgesics was seen after 6 months, 50% after 12 months, respectively. Conclusion: In this retrospective analysis, TENS has no predictive value in the selection of patients with low back pain for the PFNS treatment. PNFS is effective and safe to relieve significantly symptoms of chronic low back pain.